Resilience and the Ethics of “Big Mind” Thinking in the Tibetan Diaspora - Lewis, Sara E. (Journal of global buddhism, 2021)
Drawing on extensive ethnographic research in Dharamsala, India, this article considers how sems pa chen po (vast or spacious mind) can be understood as emblematic of the Tibetan Buddhist view of resilience. The “big mind” view acts as a kind of north star principle, guiding the way, even and especially among those who are struggling. A spacious mind is not merely an outcome, but a pathway, a method, and a horizon, orienting those who are suffering toward recovery. This article explores resilience from a perspective that suffering is inherently workable, and in fact, can be a great teacher. This argument is framed theoretically within an “anthropology of the good,” which seeks to understand resilience as moral experience; more aptly explaining what Tibetan Buddhists do in the face of adversity than the dichotomy of trauma/resilience, which is rooted narrowly in a Euro-American view of mental health.